(untitled) (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2025)
Pedagogical transformation in the digital age aligns with the digitalization program from the Indonesian Ministry of Education and Culture. The policy emphasizes using information technology tools such as tablets, computers, and home learning portals as operational support for performance schools. Learning enhanced through digitalization will bring about a variety of new learning methods that directly facilitate the learning process between educators and pupils. The topic of the study is the pedagogical transformation of English language teaching at junior high schools in the digital age in remote areas of Sambas. It was to describe the change of pedagogy in English language teaching using digital devices in a remote area. The research used a qualitative case study. The researcher used observation, interviews, and document analysis to collect data. The data were taken from remote schools in Paloh and Sejangkung. Based on the findings, the pedagogical transformation can be implemented with limited resources in remote schools of Sambas. Implementing pedagogical transformation in English language teaching gives benefits and challenges. It helps the students and the teachers in teaching and learning activities. However, no electricity line, limited internet access, and limited digital devices become the challenges for educational providers in remote areas.